MENINGKATKAN HASIL BELAJAR SISWA DENGAN PENERAPAN MODEL PEMBELAJARAN INDIVIDUAL DAN PEMBELAJARAN KOOPERATIF DI SMA SWASTA MEDAN - Siregar, Hotma Tiolina (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This researc was aimed to investigate the differences between aplication of cooperative learning model and individual model using Mini Lab in biology class withs the topic reproduction system in private schools in Medan. The metodology that using in this research is experimental method with application of cooperative learning model at class XI-A SMA YPI and at class XI-A SMA AL-washliyah, then at class XI-B SMA YPI and at class XI-B SMA AL-washliyah using individual model. The data was collected with the observation sheet, and biology test. Before hypotheses test, previously noemaly test and homogenety test were done, The result show that sample was taken from homogenic and normality population. From the data analysa showed the mean of biology test with appliction of cooperative learning model is 7,61 and standart deviation is 0,34, Meanwhile the mean of biology test with aplication of individual learning model is 6,09 and standart deviation is 0,34. Then hypotheses test with t test show hitung > t table, then ho is rejected and alternatife is excepted.Keywords: Cooperative Learning, Individual Learning Model, Mini Lab.